Understanding Brexit : why Britain voted to leave the European Union - Taylor, Graham (SocietyNow, 2017)
On 23rd June 2016 the United Kingdom shocked the world by voting to leave the European Union. In this clear and concise book, Graham Taylor argues that the result is the most visible tip of an iceberg of social change that has been decades in the making. Hidden from view are a matrix of economic, socio-cultural and political dynamics that have wrought fundamental changes to the British state and society and the relationship between the UK and the rest of the world. These dynamics include the development of an increasingly financialized economy, de-industrialization and an increasing polarization of power and wealth, the resurgence of nationalism and sub-nationalisms and the realignment of electoral politics and emergence of political populism. This book highlights the historical and multifaceted nature of Brexit and its significance for Britain's future, providing a rigorous and forensic analysis of the most dramatic event to confront contemporary British society since the Second World War.